2008
DOI: 10.1158/0008-5472.can-07-6726
|View full text |Cite
|
Sign up to set email alerts
|

An HLA-DR–Degenerate Epitope Pool Detects Insulin-like Growth Factor Binding Protein 2–Specific Immunity in Patients with Cancer

Abstract: Recent studies have shown the importance of helper CD4 T cells in initiating and sustaining tumor-specific CD8 T-cell immunity. This has paved the way for identifying MHC class II epitopes that could be incorporated into class I-based vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…All six family members are secreted and expressed in normal ovarian tissue, although previous studies have shown that IGFBP-2 serum levels and expression to be significantly increased in ovarian cancer tissue in comparison with controls [167-170]. We revealed for the first time that IGFBP-2 elicits an in vivo antigen-specific CD4 T cell immunity in patients with ovarian cancer [171]. In that study, T cells from >15% of the patients elicited a response against four HLA-DR-degenerate IGFBP-2 epitopes compared with controls.…”
Section: Targeted Antigens In Ovarian Cancermentioning
confidence: 93%
“…All six family members are secreted and expressed in normal ovarian tissue, although previous studies have shown that IGFBP-2 serum levels and expression to be significantly increased in ovarian cancer tissue in comparison with controls [167-170]. We revealed for the first time that IGFBP-2 elicits an in vivo antigen-specific CD4 T cell immunity in patients with ovarian cancer [171]. In that study, T cells from >15% of the patients elicited a response against four HLA-DR-degenerate IGFBP-2 epitopes compared with controls.…”
Section: Targeted Antigens In Ovarian Cancermentioning
confidence: 93%
“…In that experiment, peripheral blood T cells were stimulated with a pool of HLA-DR epitopes derived from the FRα or IGFBP2. Both of these antigens are highly expressed in a high percentage of patients with ovarian cancer and some patients with ovarian cancer demonstrate natural immunity to these antigens (32, 33). As shown, patients treated with MV-NIS augmented immune responses to both antigens but not to tetanus, which was added as a control for specificity of the immune response.…”
Section: Resultsmentioning
confidence: 99%
“…To detect tumor-specific T-cell immunity, a degenerate panel of peptides derived from either the folate receptor alpha (FRα; FR30, FR56, FR113, and FR238) or insulin-like growth factor binding protein 2 (IGFBP2; IGFBP2.17, IGFBP2.22, IGFBP2.249, and IGFBP2.293), as previously described, was used (32, 33). The plates were read on an AID ELISpot reader (Cell Technology, Inc.; reader software v.3.1.1.).…”
Section: Methodsmentioning
confidence: 99%
“…All six family members are secreted and expressed in normal ovarian tissue, although previous studies have shown IGFBP-2 serum levels and expression to be significantly increased in ovarian cancer tissue in comparison with controls [45–48]. We revealed for the first time that IGFBP-2 elicits an in vivo antigen-specific CD4 T-cell immunity in patients with breast and ovarian cancer [49]. In this study, T cells from more than 15% of the patients elicited a response against four HLA-DR-degenerate IGFBP-2 epitopes compared with controls.…”
Section: Antigen Specificity Of the Ovarian Cancer Immune Responsementioning
confidence: 91%